Δ13C values in archaeological 14C‐AMS dated charcoals: Assessing mid‐Holocene climate fluctuations and human response from a high‐resolution isotope record (Arslantepe, Turkey). (10th June 2018) - Vignola, C.; Masi, A.; Balossi Restelli, F.; Frangipane, M.; Marzaioli, F.; Passariello, I.; Rubino, M.; Terrasi, F.; Sadori, L.
Abstract : Rationale: Past climate has always influenced human adaptation to the environment. In order to reconstruct palaeoclimate fluctuations and their role in the evolution of Near Eastern societies during the mid‐Holocene, high‐resolution Δ 13 C records from fossil wood remains at the archaeoloical site of Arslantepe (eastern Turkey) have been developed. Methods: After chemical treatment, δ 13 C values were measured by sample combustion flow using a FLASH EA‐CHNS instrument interfaced with a Delta V isotope ratio mass spectrometer via a CONFLO III. Two replicates per sample were analysed. The measurement precision was evaluated by propagating variations of the δ 13 C values of samples and V‐PDB standards, whereas the accuracy was checked by a quality control sample. To account for changes in atmospheric CO2, Δ 13 C values were calculated. In addition, 14 C/ 12 C ratios were measured by means of an AMS system (3 MV tandem accelerator). Results: Mean Δ 13 C curves of deciduous Quercus and Juniperus from archaeological levels between 4700 and 2000 bc (Arslantepe periods VIII‐VI D) were produced, where the isotope values were ordered by the available Radiocarbon ages. Interspecific variations of evergreen vs deciduous plants were postulated for the juniper Δ 13 C values being higher than 3‰. The seasonal rainfall amount was recorded by the juniper remains, while the water table levels were obtained from the oak samples. Conclusions: The local climate experienced times of enhanced/reduced precipitation in concert with regional trends. Anomalies in the air mass circulation from the Mediterranean basin also produced oscillations of rainfall amount. In such a frame the Rapid Climate Change dry events had a consistent signature in the Arslantepe Δ 13 C record, thus potentially contributing to social or organisational changes at the site.